ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UTANG LUAR NEGERI DI INDONESIA - Defrizal Saputra; Hasdi Aimon; Melti Roza Adry (Universitas Negeri Padang, 2018)
This study aims to determine and analyze the factors that influence foreign debt in Indonesia with variables that effect economic growth, inflation, and foreign interest rates. This type of research is associative descriptive research, where the data used is secondary data from 1970 to 2017 obtained from institutions and related institutions, which are analyzed using the Error Correction Model (ECM) method. This study initially used the Ordinary Lest Square (OLS) method to see long-term, and used ECM because it wanted to see short-term at the same time. The findings of this study indicate that economic growth and inflation have a significant effect in the long run, but the interest rates have no significant effect, and in the short term all have a significant effect on foreign debt in Indonesia. Keywords: foreign debt, economic growth, inflation, interest rates and error correction model (ECM)